2001
DOI: 10.1111/j.1651-2227.2001.tb02443.x
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil counts and urinary eosinophil protein X in children hospitalized for wheezing during the first year of life: prediction of recurrent wheezing

Abstract: Children with severe wheezing during the first year of life and subsequent recurrent wheezing are characterized by a normal or high eosinophil count in response to viral infections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
30
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 28 publications
8
30
1
Order By: Relevance
“…Boesen addresses the question of whether or not asthmatic bronchitis is a forerunner of bronchial asthma. As emphasized by Korppi and Kotaniemi-Syrjänen, the results presented by Boesen in 1953 are remarkably consistent with their own results from Kuopio, Finland, five decades later (3), and also with results from Sweden and Norway (4)(5)(6).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Boesen addresses the question of whether or not asthmatic bronchitis is a forerunner of bronchial asthma. As emphasized by Korppi and Kotaniemi-Syrjänen, the results presented by Boesen in 1953 are remarkably consistent with their own results from Kuopio, Finland, five decades later (3), and also with results from Sweden and Norway (4)(5)(6).…”
supporting
confidence: 74%
“…Interestingly, Boesen points out that eosinophilia (!0.4 Â 10 9 L À1 ) was of prognostic importance (2). In recent years, the prognostic value of eosinophilia has been reported in several studies (3,6,11,12). In fact, there are studies indicating that eosinopenia may be considered to be the normal immune response to early viral infections (11,13).…”
mentioning
confidence: 97%
“…During acute viral respiratory infection, eosinopenia has been considered as a normal response [155,156], and in children with wheezing lower respiratory tract infection, blood eosinophilia or normal eosinophil counts have been predictive of persistent wheezing or asthma [142,145,[156][157][158]. In children hospitalized for wheezing, eosinophilia has been particularly associated with rhinovirus infection [51,159].…”
Section: Role Of Eosinophil Activationmentioning
confidence: 99%
“…However, u-EPX does not seem to predict persistence of wheezing or asthma [69][70][71]. Furthermore, most studies showed a large overlap in u-EPX values between symptomatic and asymptomatic children [68,[70][71][72]. There is some evidence that u-LTE 4 levels are associated with polymorphisms in the cysteinyl leukotrienes pathway genes that are in turn related to treatment responses to montelukast in preschool wheezers [73].…”
Section: Urine Analysismentioning
confidence: 99%